Esquema de gerencia estratégica sostenible para la Empresa Constructora Las Galias. (2023)
This degree project addresses the implementation of a sustainable strategic management scheme designed specifically for the Las Galias construction company. This comprehensive, future-oriented approach seeks to address the challenges and seize the opportunities presented in today's business environment. The proposed scheme is based on considering financial, commercial, internal, learning and growth aspects, as well as the Sustainable Development Goals (SDGs). The proposed strategic management scheme adapts to the particularities of Las Galias, considering its organizational structure, its target market and its strategic objectives. This ensures that the recommended strategies and actions are directly applicable to the company's reality, which significantly increases the chances of success during their implementation.